FABRICATION, MECHANICAL PROPERTIES, AND INTERFACE STRUCTURE OF RAMIE FIBER COMPOSITE - -, Sudarsono (IST AKPRIND YOGYAKARTA, 2018)
In present work, ramie fiber based composites are fabricated and tested on its mechanical properties and interface structure. The work aims to investigate effect of volume fraction of ramie fiber (VoF) on mechanical properties (yield and tensile strength, bending stress and strain, and modulus elasticity) of the composites. Besides, bonding and mixing between ramie fiber and resin are also observed under interface structure test. The VoF observed are 25, 35, 45, and 55%. The results indicate that maximum yields strength of 8.03 kgf/mm2 and tensile strength of 12.29 kgf/mm2 are obtained in the composite with VoF of 45%. Meanwhile, bending stress of 121.78 MPa and bending stress of 3.25% are observed in the composite with VoF of 55%. Although good bending between ramie and resin are occurred, but non-uniform mixing between the two is observed due to fabrication method used.